Developing a Measure of Fraternal Bullying among a Sample of Adolescents - Sabah, Aiche (Jordan Journal of Educational Sciences, 2021)
The current study aims at developing the fraternal bullying scale in a sample of adolescents, verifying its structure through the factor analysis, as well as studying the differences in the level of fraternal bullying among adolescents according to the gender and age variables, The study was conducted on a sample of 221 pupils at Chlef and Ouargla states, who were chosen accidently. To achieve the objectives of the study, the descriptive approach was used based on the fraternal bullying scale built by the researcher, which consists of 26 items and measures two images of bullying: bullying on the brothers (victim) and bullying by the (bullying) brothers and measures three sub-dimensions of each image: physical, emotional and verbal bullying. The scale was presented to a group of psychologists, after which the statistical analysis of the scale was performed on the sample study. The results showed that there was a statistically significant correlation between the items and the scale as a whole through internal consistency and indications of acceptable stability, as indicated by conformity indicators. After conducting the confirmatory factor analysis, the model enjoyed a good overall match. There were also differences in the level of bullying on the brothers (victim) in favor of females, with the absence of differences between males and females in fraternal bullying of the image of the bullying brother. The study showed the existence of differences in the level of bullying according to the age variable and after using Scheffe post hoc test, it was reached that there are differences between two groups: first adolescence and middle adolescence